Failure to Success - APJ Abdul Kalam and Arun Tiwari (Orient Blackswan, 2011)
The first attempt to launch SLV-3 was unsuccessful As expected there was a press conference immediately where reporters had many questions While Abdul Kalam felt responsible for the crash his chairman Professor Satish Dhawan took it upon himself to answer all the questions with confidence He promised the media to launch SLV-3 exactly a year later The entire team worked doubly hard to make it happen and a year later it was a grand success There was another press conference but this time Prof Satish Dhawan gave the mike to Abdul Kalam To him Prof Dhawan was an ideal and inspirational team leader